Local fracture toughness and residual stress measurements on NiAl bond coats by micro cantilever and fib-based bar milling tests - Neumeier, Steffen; Webler, Ralf; Krottenthaler, Markus; Durst, Karsten; Göken, Mathias (12th International Symposium on Superalloys, Superalloys 2012, 2012)
The mechanical behavior of bond coats depends on their chemical composition. Important for the mechanical behavior is the Al content of β-NiAl based coatings. Additionally, internal stresses are present and change during thermal cycling. Therefore bond coats with different Ni and Al content in the as-coated and thermally cycled state are investigated. For the first time, new small scaled methods are used to obtain fracture toughness and internal stresses of real bond coat systems. Micro cantilever bending and stress relaxation tests were performed on a local scale by employing focused ion beam milling. Additionally, the influence of NiAl composition on Young's modulus and hardness is studied by nanoindentation. Results show an increase of Young's modulus with Al content. In off-stoichiometric NiAl a higher hardness and fracture toughness than in binary NiAl is found. The internal stresses change from tensile in as-coated to compressive stresses in thermally cycled bond coats, respectively.
Keywords: Bond coat; FIB; Fracture toughness; Micro cantilever; Nanoindentation; NiAl; Residual stress; Thermal cycling